Crafty kids: holiday & everyday projects(festive and fun creations) - Douglas, Vincent F. (Waterbird Press : McGraw Hill Children's Pub. Ohio, 2003)
This inspiring book features decoration projects and engaging activities for many major American holidays. The artistic objects that children create will be used and admired throughout every season of the year!